Estudo da performance de processos de separação por membranas para remoção de manganês e ferro de águas - Livinalli, Nathália Ferronato (My University, 2022)
Water Treatment Plants face several problems during droughts, as a result of the intensification of water withdrawal from the lower levels of dams, where there is a higher percentage of organic matter and availability of metal ions, among them manganese and iron present in high concentrations in the water source. These metals are dissolved in water, oxygen in the water is oxidizing and precipitating the iron and manganese, because of that the appearance and taste of water change, when in excess in the body they can affect the human neurological and muscular system. These metals when dissolved in water can come into contact with oxygen from the atmosphere and oxidize, giving color and taste to the water, and when in excess in the body can affect the human neurological and muscular system. In view of this, this research aims to suggest an option for improving the treatment processes used by Brazilian public supply systems, with the addition of membrane separation processes of reverse osmosis and electrodialysis, in order to adjust the concentration of these ions in treated water to the legislation applied by the Ministry of Health in Directive 5/2017, which highlights limits of 0.1 mg.L-1 and 0.3 mg.L-1 for manganese and iron, respectively. To reach this objective, three synthetic solutions were used in the process feed, distinguished by the ions present in solution, to study the removal of metals in individual and in combination. The solutions were synthesized from two hydrated salts and named as follows: Solution A (MnSO4), B (FeSO4) and C (MnSO4 and FeSO4). In the test with the reverse osmosis membrane, the initial hydraulic permeability and compaction tests were carried out and after the retention tests with each study solution, the pressure applied in the system were 6 bar. The test with the electrodialysis technique occurred in a three-compartment system, with the cationic and anionic membrane (used alternately), with the objective of demineralizing the central compartment, and to verify the quality of the tests, prior to the retention tests, the limiting current for the system with each feed solution was determined. The two processes studied achieved promising results regarding the percentage of retention, a reverse osmosis obtained 99% retention for solution A (manganese present), 93% for B (iron present) and 98% for C (mixed solution) and electrodialysis system reached 99.76% for solution A, 98.45% for B and 99.32% for C. The electrodialysis technique was able to meet the Brazilian legislation required for the concentration of manganese and iron ions in treated water, for all the retention tests performed in the system. The Separation Process by Membranes studied were promising for the proposal to improve conventional water treatment, further deepening in this context is necessary for the actual implementation of the techniques in water treatment plants. [resumo fornecido pelo autor]
Estações de tratamento de água enfrentam diversos problemas na estiagem, em consequência da intensificação da retirada de água de níveis inferiores das barragens, onde há maior percentual de matéria orgânica e disponibilidade de íons metálicos, entre eles o manganês e o ferro presentes em altas concentrações na água a ser tratada. Esses metais quando dissolvidos na água podem entrar em contato com oxigênio da atmosfera e oxidar, originando cor e sabor à água e quando em excesso no organismo, podem afetar o sistema neurológico e muscular humano. À vista disso, a pesquisa em questão, pretende sugerir uma opção de melhoria aos processos de tratamento utilizados pelos sistemas de abastecimento público brasileiro, com a adição dos processos de separação por membranas de osmose inversa e eletrodiálise, a fim de adequar a concentração desses íons na água tratada à legislação aplicada pelo Ministério da Saúde na Portaria 5/2017, que destaca limites de 0,1 mg.L-1 e 0,3 mg.L-1 para manganês e ferro respectivamente. Para alcançar esse objetivo, foram utilizadas três soluções sintéticas na alimentação do processo, diferenciadas pelos íons presentes em solução, para o estudo da remoção isoladamente e em conjunto dos metais. As soluções foram sintetizadas a partir de dois sais hidratados e nomeadas como segue: Solução A (MnSO4), B (FeSO4) e C (MnSO4 e FeSO4). No teste com a membrana de osmose inversa, previamente realizou-se ensaios de compactação e permeabilidade hidráulica inicial e após os testes de retenção com cada solução de estudo, a pressão aplicada no sistema foi de 6 bar. O teste com a técnica de eletrodiálise ocorreu em um sistema de três compartimentos, com a membrana catiônica e aniônica (utilizadas de forma alternadas), com o objetivo de desmineralização do compartimento central, e para verificar a qualidade dos testes, anteriormente aos ensaios de retenção, foi determinada a corrente limite para o sistema com cada solução de alimentação. Os dois processos estudados atingiram resultados promissores quanto ao percentual de retenção total de íons, a osmose inversa obteve 99 % de retenção para a solução A, 93 % para a B e 98 % para a C e o sistema de eletrodiálise chegou a 99,76 % para solução A, 98,45 % para B e 99,32 % para a C. A técnica de eletrodiálise foi capaz de atender a legislação brasileira exigida para a concentração dos íons manganês e ferro em água tratada, para todos os testes de retenção realizados no sistema. Os Processos de Separação por Membranas estudados foram promissores para a proposta de aprimorar o tratamento de água convencional, é necessário maior aprofundamento neste contexto para a implementação real das técnicas em estações de tratamento de água. [resumo fornecido pelo autor]
Keywords: Engenharia química; Água - Purificação; Osmose inversa; Eletrodiálise